The Silent Suffering of Jane Doe: Negligence of Mental Health Problems in Daily Practice - Julius Kremling (University Library System, University of Pittsburgh, 2015)
Every day health care professionals ignore their patients' need for socia-psychological support. This article describes the author's personal experiences with this deficit in health care.